PENINGKATAN KETERAMPILAN MEMBACA PUISI MELALUI MEDIA AUDIO VISUAL OLEH SISWA KELAS X SMA NEGERI 1 LAWE BULAN TAHUN PELAJARAN 2021/2022 - Andriani Andriani; Ati Rosmiati (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the improvement of poetry reading skills through audio visual media. By Class X Students of SMA Negeri 1 Lawe Month of the 2021/2022 Academic Year. Based on the results of the research and discussion that have been described in the previous chapter, it can be concluded that there is an increase in reading skills of Ws.Rendra's poems from the sun by using Audio Visual Media by class X students of SMA Negeri 1 Lawe Bulan in the 2021/2022 academic year. It can be proven from the average score of the initial test of students' poetry reading skills is 70.91 with a standard deviation of 3.66 and an increase in the value of the final test results with an average value of 79.32 with a standard deviation of 5.33. Based on the data from the results of the students' initial and final tests and if it is associated with the Indonesian KKM score for SMA of 75, the students' ability to read the poem "Sajak Matahari" can be said to be good after audio-visual media in the form of youtube videos are performed. In addition, at a value of > 12.63 > 1.720, therefore from the results of testing the hypothesis above, it can be concluded that there is an increase in Poetry Reading Skills through Audio Visual Media. By Class X Students of SMA Negeri 1 Lawe Month of the 2021/2022 Academic Year.